Bioinspired origami-based soft prosthetic knees - Siyuan Gao; Chengxu Yang; Hongting Chen; Xinqiang He; Lecheng Ruan; Qining Wang (Nature Communications)
Abstract Prosthetic knees represent a prevalent solution for above-knee amputation rehabilitation. However, satisfying the ambulation requirements of users while achieving their comfort needs in terms of lightweight, bionic, shock-absorbing, and user-centric, remains out of reach. Soft materials seem to provide alternative solutions as their properties are conducive to the comfort aspect. Unfortunately, the pronounced flexibility restricts the application of soft robots on prosthetic knees regarding morphological computation and weight-bearing performance. Here, we innovate a soft prosthetic knee for transfemoral amputees, addressing current challenges through the integration of origami technology and bioinspired weight-bearing principle, achieving its lightweight, compactness, low cost, and simple fabrication. The soft knee can hold the weight of a human (more than 75 kg), perform biomimetic polycentric flexion, absorb impacts during walking (absorbing 11.5% to 17.3% more impact forces), and actively support amputees to walk across ramps, stairs, and obstacles. The efficacy of the proposed design has been corroborated through bench-top and ambulation experiments. The proposal might lead to a paradigm shift in the lower limb prosthetic design.